Thank you, Mr. Falker - Polacco, Patricia (New York : Scholastic Inc., 1999)
At first, Trisha loves school, but her difficulty learning to read makes her feel dumb, until, in the fifth grade, a new teacher helps her understand and overcome her problem.
Keywords: Reading -- Juvenile fiction; Teachers -- Juvenile fiction; Self-perception -- Juvenile fiction